Social judgments on abortion and contraceptive use: a mixed methods study among secondary school teachers and student peer-counsellors in western Kenya - Miranda Håkansson; Stephanie Super; Monica Oguttu; Marlene Makenzius (BMC, 2020)
Abstract Background In Kenya, unsafe abortion is the leading cause of maternal deaths in adolescent girls aged 15-19 years, and a majority did not use a modern contraceptive before becoming pregnant. The aim of this study was to explore attitudes related to abortion and contraceptive use among secondary school teachers and student peer-counsellors in a low-resource setting in western Kenya. Methods A mixed methods design, combining a questionnaire-survey and focus group discussions (FGDs), was utilised to explore attitudes to abortion and contraceptive use among teachers (n = 15) and student peer-counsellors (n = 21) at a secondary school in Kisumu, Kenya. First, two Likert scale questionnaires were used: a modified version of the Stigmatising Attitudes, Beliefs and Actions (SABA) scale and the Contraceptive Use Stigma (CUS) scale. Secondly, four FGDs were conducted. Descriptive statistics and Abductive Thematic Network Analysis (ATNA) were used to analyse the data. Results Overall, Social judgments on abortion and contraceptive use were found among teachers and student peer-counsellors, with similar patterns between sexes. Christian and cultural values; A majority, 28/36 considered abortion a sin, and chastity and purity before marriage were highly valued feminine ideals. Discrimination and isolation; 18/36 believed that a girl who has had an abortion might be a bad influence on other girls, and 13/35 stated that an adolescent girl cannot decide for herself if to use a contraceptive method. Conflicting views on abortion and contraceptives; A third (11/34) believed that contraceptives may cause infertility, and its use was related to promiscuity. Girls associated with abortion and contraceptive use were considered immoral, lacking parental guidance, and were used to represent bad examples in school. Although conflicting views were present, sexuality was considered a taboo topic, which left adolescents ignorant on contraceptive use. Conclusions Adolescent girls associated with abortion and contraceptive use are at risk for social judgements and discrimination, by both peers and teachers. Sexual and reproductive health training needs to be implemented in teacher education to increase knowledge on adolescent sexuality, abortion and contraceptive use to improve adolescents' sexual health and decrease the stigma. Trial registration This was a prestudy nested in a cluster randomised intervention study, registered on February 28, 2017, at ClinicalTrials.gov ( NCT03065842 ).